2022
DOI: 10.3389/fphar.2022.891954
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Stakeholders’ Views on Pharmacovigilance System, Policy, and Coordination in Pakistan

Abstract: Objectives:Due to the absence of necessary rules, poor coordination, and various challenges, the pharmacovigilance system of Pakistan is not optimally functional at all levels of the health system. The objective of the study was to assess the stakeholders’ perceptions of the current ADR reporting system and to identify the pharmacovigilance policy issues and problems of effective coordination.Methodology:Stakeholders from a broad range of disciplines, academia, regulatory authorities, the pharmaceutical indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“… 28 , 33 In addition, there is a need for a policy framework, incorporating communication and decentralization strategies to ensure sustainable integration of the pharmacovigilance system at the PHPs and health facilities. 35 …”
Section: Discussionmentioning
confidence: 99%
“… 28 , 33 In addition, there is a need for a policy framework, incorporating communication and decentralization strategies to ensure sustainable integration of the pharmacovigilance system at the PHPs and health facilities. 35 …”
Section: Discussionmentioning
confidence: 99%
“…A study of Pakistan’s pharmacovigilance system conducted in 2020 also found that the system was not fully functional. 9 , 10 …”
Section: Pharmacovigilance System Strengthening In Pakistanmentioning
confidence: 99%
“…A study of Pakistan's pharmacovigilance system conducted in 2020 also found that the system was not fully functional. 9,10 Pakistan's regulatory policies regarding the authorization of COVID-19 vaccines and related pharmacovigilance were also identified to be insufficient. In April 2021, the Ministry of National Health Services, Regulations and Coordination (MONHSRC) developed but never adopted national guidelines for surveillance of COVID-19 vaccine AEFIs.…”
Section: Pharmacovigilance System Strengthening In Pakistanmentioning
confidence: 99%